Transition Design in Latin America: Enabling Collective Learning and Change - Juri, Silvana; Zurbriggen, Cristina; Bosch Gómez, Sofía; Ortega Pallanez, Marysol (Frontiers in Sociology, 2021)
Latin American societies currently confront numerous social, economic, and environmental issues. The complex and interlinked nature of these issues demands responses that fully and equally engage with the social and environmental domains in creative and integrative ways that blur traditional dichotomies and disciplinary boundaries. Most importantly, they need to weave in and reflect the plurality and specificity of the contexts in an autonomous and non-colonialist fashion. In this paper, we draw inspiration from approaches that emerged in the Global North such as Resilience Thinking, Policy Design, and Transition Design, all of which strive for knowledge plurality and synthesis applied to systemic transformational processes. To contribute to this pluralistic motivation and to promote critical reflection and learning, in this work we outline the main contributions of such approaches and have them converse with Latin American perspectives and practices. Through the application of a Transition Design lens, a practice-oriented perspective aimed at catalyzing societal transitional processes towards sustainable futures, we act as practitioners and interlocutors that adopt, adapt, and expand its theoretical and methodological applications in collective learning spaces, processes, and platforms. The action-oriented nature of this approach allows us to analyze particular cases of application, their contexts, and their theoretical or methodological nuances which determine their potential or degree of success in generating actual change. The structure of this article moves from outlining and introducing the main frameworks and notions relevant for adopting a Transition Design approach in Latin America, to describing cases developed in different pedagogical or action-research platforms, culminating with a collection of reflections stemming from our experiences applying Transition Design in Latin America. The first section offers a theoretical compass to expand a more robust framework that supports and enables socio-environmental transitions in the region. The second part presents three case studies to illustrate the application and interpretation of different methods and the challenges and opportunities presented. We conclude by offering insights into potential future pathways for embracing and deepening holistic and systemic approaches like Transition Design in Latin American settings.